VD_FINDINFO Jug / 2014 / 209 vom 25. September 2013 - VD Tribunal cantonal (2013)
VIOL, CONJOINT, APPRÉCIATION DES PREUVES, FIXATION DE LA PEINE, SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE | 190 CP, 43 CP, 47 CP, 10 CPP (CH)